2021
DOI: 10.1136/bmjgh-2021-007168
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the cost-effectiveness of essential and advanced critical care for COVID-19 patients in Kenya

Abstract: BackgroundCase management of symptomatic COVID-19 patients is a key health system intervention. The Kenyan government embarked to fill capacity gaps in essential and advanced critical care (ACC) needed for the management of severe and critical COVID-19. However, given scarce resources, gaps in both essential and ACC persist. This study assessed the cost-effectiveness of investments in essential and ACC to inform the prioritisation of investment decisions.MethodsWe employed a decision tree model to assess the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…This, therefore, implies that there is a need for preparedness; prioritization of supplemental oxygen support in general hospital wards to handle more of the severe cases. The findings of our study agree with those of Kairu et al ( Kairu et al, 2021 ); that the priority of investments should be on essential care for COVID-19 cases with severe infections. Our study is also comparable to that of Musa et al ( Musa et al, 2021 ) which recommended forecasting as an important tool to inform future epidemiological investigations and mitigation plans.…”
Section: Resultssupporting
confidence: 93%
“…This, therefore, implies that there is a need for preparedness; prioritization of supplemental oxygen support in general hospital wards to handle more of the severe cases. The findings of our study agree with those of Kairu et al ( Kairu et al, 2021 ); that the priority of investments should be on essential care for COVID-19 cases with severe infections. Our study is also comparable to that of Musa et al ( Musa et al, 2021 ) which recommended forecasting as an important tool to inform future epidemiological investigations and mitigation plans.…”
Section: Resultssupporting
confidence: 93%
“…Of the remaining seven un-pooled studies about COVID-19 treatment, two concluded that COVID-19 vaccinations were cost-effective [ 11 , 102 - 105 ]. For lower-income economies like Kenya, investments in essential care before advanced critical care should be prioritised [ 106 ], and only one study reported general ward and intensive care was not cost-effective compared to general ward only [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ferguson et al [ 108 ] suggested that suppression was the preferred policy option for countries that could achieve it, which is consistent with our results and explains the source of heterogeneity. With the rapid transmission speed of new variants and in contexts of weaker health systems, along with the greater vulnerability of developing economies to the negative impact of stringent measures, the trade-offs faced by low-income countries are complex [ 106 , 109 ]. In addition, low-income states lack the infrastructure for implementing technology-led containment strategies [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lack of availability and access of critical care across Tanzania, such novel approaches may provide a building block to developing a fully resourced, equitable critical care system. 60 However, decision makers require further evidence on the optimal design, costs, budget impact and cost-effectiveness of such critical care interventions in rural and urban systems.…”
Section: Discussionmentioning
confidence: 99%